Correlation of motor-auditory cross-modal and auditory unimodal N1 and mismatch responses of schizophrenic patients and normal subjects: an MEG study - Okazaki, Mitsutoshi; Yumoto, Masato; Kaneko, Yuu; Maruo, Kazushi (Frontiers in Psychiatry, 2023)
It has been suggested that the positive symptoms of schizophrenic patients (hallucinations, delusions, and passivity experience) are caused by dysfunction of their internal and external sensory prediction errors. This is often discussed as related to dysfunction of the forward model that executes self-monitoring. Several reports have discussed that the dysfunction of the forward model in schizophrenia causes misattributions of self-generated thoughts and actions to external sources. There are some evidences that the forward model can be measured using electroencephalography (EEG) and magnetoencephalography (MEG) components such as N1(m) and mismatch negativity (MMN) (m). In our MEG study, we investigated differences in the N1m and MMNm-like activity generated in the motor-auditory cross-modal task in normal control subjects (NC) and schizophrenic patients (SC), and compared that activity with the N1m and MMNm in the auditory unimodal task. We found that (i) there was no significant difference in N1m-attenuation for the NC and SC groups, and that (ii) MMNm in the unimodal task in the SC group was significantly smaller than that in the NC group. Moreover, the MMNm-like activity in the cross-modal task was smaller than the MMNm in the unimodal task in the NC group, but there was no significant difference in the SC group. The PANSS positive symptoms and general psychopathology score were moderately negatively correlated with amplitudes of MMNm-like activity, and the antipsychotic drug dosage was moderately negatively correlated with the N1m suppression rate. However, none of these reached statistical significance. Our findings suggest that schizophrenic patients perform altered predictive process differently from healthy subjects in latencies reflecting MMNm, depending on whether they are under forward model generation or not. This may support the hypothesis that schizophrenic patients tend to misattribute their inner experience to external agents, thus leading to their characteristic symptoms.